The Effect of Knowledge Management in Job performance A Field Study in the private Commercial Banks in the Syrian Coast (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The aim of the research is to determine the effect of Knowledge Management (Knowledge Generation, Knowledge Storage, Knowledge Distribution, Knowledge Applying) in Job Performance in the private commercial banks in the Syrian coast. The researcher relied on the descriptive analytical approach as a general approach to research. A questionnaire was designed and distributed to a sample of 117 employees at all administrative levels in a number of private commercial banks in the Syrian coast (105 valid questionnaire for statistical analysis). And the researcher used the statistical program (SPSS) in conducting statistics and testing research hypothesis. the research found several results, the most important of them: that the degree of applying of knowledge management by private commercial banks in the Syrian coast is moderate, and that the level of job performance of employees is moderate, and there is a positive significant effect for the knowledge management in job performance.